Serious leisure, self-perceptions and everyday creativity - Elisondo, Romina Cecilia (2018)
he article includes two studies, the first analyses relationships between participation in leisure and creativity. Five hundred sixty-two men and women from Córdoba (Argentina) participate in the first study. The participants´ ages range from 18 to 60 years. The instruments of data collection are Creative Actions Scale, Test CREA, Test of Unconventional Uses and Leisure Activities Questionnaire. The aim of Study 2 is to investigate self-perceptions about creativity and analyses activities where people develop creative processes. In Study 2 participate two hundred five persons who has been surveyed in Study 1. The data collection instrument is a survey with open-ended questions. The results indicate positive effects of serious leisure activities on creativity. Participants who consider themselves creative obtain the highest mean scores in all measures of creativity. Qualitative analysis indicated that most participants consider themselves as creative in different activities and think that leisure activities are opportunities to develop creativity.